A pattern of care analysis: Prosthetic rehabilitation of head and neck cancer patients after radiotherapy. (29th April 2020) - Wiedenmann, Felicitas; Liebermann, Anja; Probst, Florian; Troeltzsch, Matthias; Balermpas, Panagiotis; Guckenberger, Matthias; Edelhoff, Daniel; Mayinger, Michael
Abstract: Background: While some medical associations provide guidelines for the implant‐prosthetic rehabilitation of head and neck cancer patients, the circulation and implementation in the everyday routine of practicing dentists remain unknown. Purpose: To analyze patterns of care for the prosthetic rehabilitation of head and neck cancer patients after radiotherapy in German speaking countries. Materials and methods: An online survey consisting of 34 questions separated into three sections, (a) general inquiries, (b) treatment concepts, and (c) patient cases, was forwarded to university hospital departments for Prosthetic Dentistry and Oral and Maxillofacial Surgery, and members of different medical associations. Statistical differences between groups were analyzed using chi‐squared test ( P  < .05). Results: From May to October 2019, 118 participants completed the survey. The majority practiced in university hospitals, had more than 5 years of work experience, and reported to be involved in <10 post radiation prosthetic rehabilitation cases per year. Rehabilitation protocols involving dental implants were implemented by oral/oral‐ and maxillofacial surgeons and prosthetic dentists, while general dentists favored implant‐free solutions. Xerostomia was recognized as a common problem for a successful prosthetic rehabilitation. The subsequent treatment choice with either fixed dental prostheses or removable dentures was divided among participants. Conclusions: As treatment planning differed with regard to the participants' field of expertise and work environment, and most practitioners only handle a low number of cases, patients might benefit from centralization in larger institutes with a multidisciplinary structure. A high agreement between the practitioners' treatment concepts and the current state of research was observed. While the choice between a mucosa‐ or tooth‐supported, and an implant‐supported restoration depends on numerous individual factors, guidelines derived from longitudinal studies would enhance evidence‐based treatment in this field.